2017
DOI: 10.1016/j.prevetmed.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Bovine tuberculosis in Ethiopia: A systematic review and meta-analysis

Abstract: Bovine tuberculosis (bTB) is a known endemic disease of cattle in Ethiopia; however, there is lack of a comprehensive information on the status and distribution of the disease in the country. The objectives of this systematic review and meta-analysis were to provide a pooled prevalence estimate of bTB at a national level, assess the level of in-between variance among study reports and illustrate the spatial distribution pattern in the country. Articles published on bTB from January 2000 to December, 2016 in En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 64 publications
(42 reference statements)
3
61
0
Order By: Relevance
“…Analysis of variance (ANOVA) tests were run on all moderators to assess their significance when compared to the full model with all other variables included. For the purposes of variable selection, given the low power of these tests and precedence set in other systematic reviews and meta‐analyses, variables with a p ‐value < 0.25 were retained for inclusion in the final model (Sibhat et al., ) (Asmare et al., ) (Dohoo, Martin, & Stryhn, ).…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of variance (ANOVA) tests were run on all moderators to assess their significance when compared to the full model with all other variables included. For the purposes of variable selection, given the low power of these tests and precedence set in other systematic reviews and meta‐analyses, variables with a p ‐value < 0.25 were retained for inclusion in the final model (Sibhat et al., ) (Asmare et al., ) (Dohoo, Martin, & Stryhn, ).…”
Section: Methodsmentioning
confidence: 99%
“…In Ethiopia, the average prevalence of bovine tuberculosis based on studies done between 2000 and 2016 showed to be 6% in cattle. The prevalence also varied based on the breeds of cattle and the production systems ( 7 ). The fact that M. bovis is frequently isolated from various animal organs/tissues such as lesions in the lungs and lymph nodes at slaughterhouses gestures that the disease can spread through both direct and indirect modes to human ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in Ethiopia reported variable (0%-16%) prevalence of M. bovis in extrapulmonary TB patients (8,9). A second possible reason could be the low prevalence of bovine TB in zebu cattle, which comprise >95% of the cattle population of Ethiopia (10) and have been reported to have lower infection rates with M. bovis than other types of cattle. In addition, most cattle husbandry in Ethiopia is on extensively managed small farms in open fields, which poses a low risk for the spread of bovine TB (7).…”
mentioning
confidence: 99%